1997
DOI: 10.1093/genetics/147.3.1191
|View full text |Cite
|
Sign up to set email alerts
|

Incipient Speciation by Sexual Isolation in Drosophila melanogaster: Extensive Genetic Divergence Without Reinforcement

Abstract: The collection of Drosophila melanogaster from Zimbabwe and nearby regions (the Z-type) yield females who would not mate with the cosmopolitan D. melanogaster males (the M-type). To dissect the genetic basis of this sexual isolation, we constructed 16 whole-chromosome substitution lines between two standard Z- and M-lines. The results were as follows: (1) All substitution lines appear normal in viability and fertility in both sexes, indicating no strong postmating isolation. (2) The genes for the behaviors are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…These findings fit within a body of studies that have identified either male or female choice of sensory signals as critical for sexual isolation among Drosophila species (patterns reviewed Yukilevich and Patterson 2019). In Drosophila melanogaster , many studies have found that male choice of specific female CHC compounds play a role in isolation between closely related heterospecifics (Coyne et al 1995, Billeter et al 2009) as well as between intraspecific populations (Wu et al 1995, Hollocher et al 1997, Yukilevich and True 2008). Such patterns of CHC-mediated male mate-discrimination have also been associated with allelic variation in CHC elongases.…”
Section: Discussionmentioning
confidence: 99%
“…These findings fit within a body of studies that have identified either male or female choice of sensory signals as critical for sexual isolation among Drosophila species (patterns reviewed Yukilevich and Patterson 2019). In Drosophila melanogaster , many studies have found that male choice of specific female CHC compounds play a role in isolation between closely related heterospecifics (Coyne et al 1995, Billeter et al 2009) as well as between intraspecific populations (Wu et al 1995, Hollocher et al 1997, Yukilevich and True 2008). Such patterns of CHC-mediated male mate-discrimination have also been associated with allelic variation in CHC elongases.…”
Section: Discussionmentioning
confidence: 99%
“…We next tested if patterns of diversity, differentiation, and population structure correspond to Z and M mating types within D. melanogaster (as described in [30, 32]). While Z mating behavior seems largely restricted to Subtropical Africa, previous work has identified that female mate choice is likely variable in the ancestral range of D. melanogaster [34] —however, the frequency of Z behavior within the ancestral range, as well as it’s phylogenetic distribution among Subtropical African flies, is largely unknown.…”
Section: Methodsmentioning
confidence: 99%
“…We used the aforementioned estimates of F ST calculated in 1KB windows between all Central Africa (including all lines, regardless of phenotype) and each OOA geographic region (Asia, Europe, North Africa, North America, and Tazmania), as well as F ST between Central Africa and each within-Africa geo-genetic lineage (West, East, Ethiopia, South, and HD). This analysis enabled us to determine whether Central Africa broadly shows increased differentiation for regions associated with female choosiness, in line with a polygenic genetic basis of female mate preference [30, 31]. We then performed an ANOVA with Type III SS to assess whether F ST differed between locus type (genome-wide versus behavioral PBE outlier), between comparison (each geographic region), and their interaction using the car package in R [57].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations